(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2023)
This study critically examines the multifaceted challenges encountered by nursing specialists in Saudi Arabia and explores capacity coverage interventions to deal with these troubles. The Kingdom of Saudi Arabia faces a myriad of hurdles inside its nursing quarter, which include a scarcity of qualified nursing workforce, inadequate education and academic opportunities, challenging work environments, socio-cultural complexities, and technological constraints. This research illuminates the complex panorama of those challenges, highlighting their effect on healthcare transport and nursing practice within the Saudi context. Additionally, this study scrutinizes existing policy frameworks related to nursing and benchmarks in opposition to international first-rate practices to pick out gaps and possibilities for improvement. Through an evaluation of the identified demanding situations, this study proposes a comprehensive set of policy hints aimed at mitigating those obstacles. These tips embody techniques for boosting education and schooling programs, imposing effective recruitment and retention projects, addressing administrative center troubles, fostering cultural sensitivity, and leveraging technology for stepped-forward nursing practices. Furthermore, this research outlines a roadmap for the implementation of these coverage interventions, emphasizing stakeholder engagement, an established timeline, and mechanisms for evaluation and monitoring. The findings of this observation not simplest contribute to the know-how of the demanding situations confronting nursing in Saudi Arabia but additionally offer actionable policy insights that can doubtlessly transform the nursing landscape, ultimately improving the great of healthcare delivery inside the Kingdom.